Le conflit fédéral-provincial au Canada : raisons et solutions - Robertson, Gordon (Les Cahiers de droit, 1985)
The author seeks to identify why Canada, as a country, has not faired out well in recent years and finds that the source of our problems lie deep in the mechanisms of federal-provincial relations. Four factors make these relations difficult : the differences flowing from distinct ethnic and linguistic origins, inadequacy of various institutions of our central government, the unclear and uneasy balance of federal-provincial powers and the extent of activity by our governments that are pressing at the outer limits of their jurisdictions.